2014
DOI: 10.1523/jneurosci.2966-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Potentiation and Learning a Whisker-Based Object Localization Task with a Time Response Window

Abstract: Whisker-based object localization requires activation and plasticity of somatosensory and motor cortex. These parts of the cerebral cortex receive strong projections from the cerebellum via the thalamus, but it is unclear whether and to what extent cerebellar processing may contribute to such a sensorimotor task. Here, we subjected knock-out mice, which suffer from impaired intrinsic plasticity in their Purkinje cells and long-term potentiation at their parallel fiber-to-Purkinje cell synapses (L7-PP2B), to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
54
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 55 publications
4
54
0
Order By: Relevance
“…4) and eyeblink conditioning (Fig. 6), but probably also for more complex, timing-sensitive processes involved in cognition and episodic memory formation (Ben-Yakov and Dudai 2011; Rahmati et al 2014 (Galliano et al 2013b), but the very same mutants start to show phenotypes in decision making when tight temporal response windows are inserted in go/nogo tasks (Rahmati et al 2014). Likewise, the timing function of the olivocerebellar system is essential when acute reflexes need to be engaged following perturbations (Van Der Giessen et al 2008).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…4) and eyeblink conditioning (Fig. 6), but probably also for more complex, timing-sensitive processes involved in cognition and episodic memory formation (Ben-Yakov and Dudai 2011; Rahmati et al 2014 (Galliano et al 2013b), but the very same mutants start to show phenotypes in decision making when tight temporal response windows are inserted in go/nogo tasks (Rahmati et al 2014). Likewise, the timing function of the olivocerebellar system is essential when acute reflexes need to be engaged following perturbations (Van Der Giessen et al 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Over the past decades, it has gradually become clear that each module is concerned with control of specific tasks, such as execution of limb and finger movements, of trunk movements for balance, of compensatory eye movements about particular axes in space, reflexes of facial musculature, homeostasis of particular autonomic processes, and probably even specific cognitive tasks, such as time-sensitive decision making (De Zeeuw et al 1994;Ito 2008;Jörntell et al 2000;Apps and Hawkes 2009;Rahmati et al 2014). However, it was not until recently that the specific intrinsic properties of different categories of modules emerged (Zhou et al 2014).…”
mentioning
confidence: 99%
“…However, the importance of these signals as it relates to behavior or learning the task is not clear and may not relate to learning the pole discrimination task at all. However, it is possible that these signals help enforce proper timing of the task, including reward licking (Rahmati et al 2014). Moving forward, combining the ability to chronically image Ca 2ϩ with optogenetic control of the inferior olive should allow for both disruption of the lick-based Ca 2ϩ events and monitoring of the resulting behavior.…”
Section: Discussionmentioning
confidence: 99%
“…LTP in these areas is assumed to be related to the consolidation of fear memories (Gao et al, 2012), akin to the function of an LTP mechanism that takes place in amygdala and hippocampus (Bliss and Collingridge, 2013;Rogan et al, 1997;Sacchetti et al, 2001). However, a recent study in cerebellar mouse mutants has shown that impairments in Purkinje cell plasticity did not affect fear responses during Page 5 of 38 A c c e p t e d M a n u s c r i p t 5 both cued and contextual conditioning (Galliano et al, 2013), even though it did result in learning deficits when a cognitive task with temporal constraints was employed (Rahmati et al, 2014). These results suggest that the cerebellum is essentially concerned with tasks requiring precise temporal accuracy (Rahmati et al, 2014;Yamaguchi and Sakurai, 2014).…”
mentioning
confidence: 99%
“…Furthermore, many fear learning paradigms involve sensorimotor and timing components next to emotional learning (Glickstein et al, 2009;Rahmati et al, 2014), thus further obfuscating the investigation into the primary role of the cerebellar regions in the purely emotional, non-motor aspects of the fear learning process. As a result, a decisive account of the precise regions and Page 6 of 38 A c c e p t e d M a n u s c r i p t 6 functional contribution of the cerebellum involved in human fear learning remains to be determined.…”
mentioning
confidence: 99%